Effects of Cottonseed Cake Based Diets on Haematology and Serum Biochemistry of Egg-Type Chickens - Adeyemo, G.O. (International Journal of Poultry Science, 2007)
The study evaluated the performance of layers fed on diets in which CSC replaced SBC in five experimental rations. The design of the experiments was Completely Randomized Design (CRD). There were 5 diets, in each experiment such that 0% (control), 15%, 30%, 45% and 60% of CSC replaced SBC. Chemical analysis was carried out to determine the Crude Protein (CP) and gossypol content of CSC. Seventy-five 23 week-old layers were fed with experimental layer diets for 12 weeks. Blood samples were collected and analyzed for differential white blood cell count (lymphocyte) and haemoglobin (Hb). All data were analyzed using descriptive statistics and analysis of variance. The determined CP of CSC was 35.11% and its gossypol content was 570g/ton, FCR ranged from 1.6 to 4.9. Values of lymphocyte and Hb ranged from 35.2% to 54.0% and 8.5g/dl to 11.1g/dl respectively. Birds on 60% CSC based diets had blood profile comparable to the control than those of other diets. CSC can replace up to 60% SBC without adverse effects on haematology and serum biochemistry of the Egg-type chickens.